Oxidation film with corrosion resistance and scale inhibition and preparation process
By using electrolytes of oxalic acid, boric acid and citric acid on the surface of the aluminum alloy for anodization, a corrosion-resistant and scale-resistant oxide film is formed, which solves the problems of corrosion and scale-resistant aluminum alloy in application, achieving higher corrosion resistance and scale-resistant, and is also environmentally friendly and economical.
Patent Information
- Application Number
- CN202411727748.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
Aluminum alloys are prone to corrosion and scale resistance problems in applications, and the corrosion resistance and scale resistance of existing oxide films still need to be improved.
Anodic oxidation technology is used to make an electrolyte by mixing oxalic acid, boric acid and citric acid, and anodic 6063 aluminum alloy workpieces are anodic to form an oxide film that is corrosion-resistant and scale-resistant.
It improves the corrosion resistance and scale resistance of the aluminum alloy oxide film, has a simple process, less waste liquid emission, less environmental pollution, and is low cost.
Smart Images

Figure CN119530919A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anodic oxidation, and relates to a corrosion-resistant and scale-inhibiting oxide film, and in particular to a simple and pollution-free anodic oxidation technology. The prepared oxide film has bright color and ceramic texture. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The density of aluminum alloy is about one-third of that of steel, but its strength is comparable to that of steel, which makes aluminum alloy widely used as a structural material in industries such as aerospace and automobile manufacturing, helping to reduce structural weight and improve fuel efficiency. Aluminum alloy has excellent electrical and thermal conductivity, so it is suitable for the production of equipment such as power transmission, radiators, and heat exchangers. Aluminum alloy is easy to process into a variety of shapes and can be processed by forging, extrusion, rolling and other processing methods, making it suitable for manufacturing parts with complex structures. Aluminum alloy has extremely high recycling value, low energy consumption when recycled and reused, and less impact on the environment, so it occupies an important position in the field of sustainable development.
[0004] Since aluminum itself has a relatively active chemical property, it is easily oxidized in the air, forming an oxide film on the surface of the substrate, which can protect the aluminum substrate. However, the density of this oxide film is insufficient and the thickness is relatively thin. In the application of heat exchange tubes, aluminum alloys often face corrosion and scale inhibition problems. Therefore, through surface modification technology, the corrosion resistance and scale inhibition of aluminum alloys can be improved. Anodizing technology has become one of the most widely used surface treatment methods due to its advantages such as low technical difficulty, simple operation and significant effect.
[0005] The paper "Anodizing of 6061 Aluminum Alloy in Oxalic Acid-Citric Acid" discloses the anodizing of 6061 aluminum alloy using a mixed solution of oxalic acid and citric acid. The effects of temperature, anode current density and electrolyte composition on the corrosion resistance of the oxide film after coloring were studied, and the optimal process conditions were obtained. However, the corrosion resistance and anti-scaling performance of the oxide film still need to be improved. Summary of the invention
[0006] In order to solve the above problems, the present invention provides an oxide film with corrosion resistance and scale inhibition and a preparation process. Taking 6063 aluminum alloy as the research object, an anodizing technology is used to prepare a corrosion-resistant and scale-inhibiting oxide film on its surface. The purpose of the present invention is to provide a surface modification technology with simple process, less waste liquid discharge, less environmental pollution and low cost.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention provides a process for preparing an oxide film having corrosion resistance and scale inhibition properties, comprising:
[0009] Cleaning the aluminum alloy workpiece;
[0010] Mix 10-80 g / L oxalic acid, 20-70 g / L boric acid and 10-60 g / L citric acid to prepare an electrolyte;
[0011] Anodizing the cleaned aluminum alloy workpiece in the electrolyte to obtain an oxide film;
[0012] The oxide film is sealed to obtain the product.
[0013] According to the composition of the electrolyte, the aluminum alloy anodizing system can be divided into a single acid system and a multi-acid mixed acid system. By adjusting the composition of the electrolyte and the process conditions, oxide films with different structures and properties can be prepared. However, due to the wide variety of inorganic acids and organic acids, the effects after compounding vary. At present, a multi-acid mixed acid system that can significantly improve the corrosion resistance and scale inhibition of aluminum alloy oxide films has not yet been found. To this end, the present invention aims to explore a new high-performance, environmentally friendly anodizing process suitable for aluminum alloys, and provide a theoretical and experimental basis for its promotion and application. After systematic research and long-term experiments, it was found that the use of weak acids oxalic acid and boric acid instead of strong acid sulfuric acid, and the addition of organic citric acid, can effectively improve the corrosion resistance and scale inhibition of aluminum alloy oxide films.
[0014] In some embodiments, the cleaning includes: water cleaning, alcohol cleaning, alkali cleaning, and acid cleaning.
[0015] In some embodiments, the specific steps of the alkaline washing include: using 1-10 mL / L NaOH aqueous solution, washing under the assistance of ultrasound for 10-15 minutes, and then washing with water and alcohol.
[0016] In some embodiments, the specific steps of pickling include: using a mixture of 1-10 mL / L HNO3 and 1-10 mL / L HF aqueous solution in a water bath at 40-60°C for 2-5 minutes, followed by water washing and alcohol washing.
[0017] In some embodiments, the anodization uses a hanging method to connect graphite and a sample, wherein the graphite serves as a cathode and the aluminum alloy workpiece serves as an anode.
[0018] In some embodiments, the anodization temperature is 25° C. to 60° C., the voltage is 20 to 50 V, and the time is 1 h to 3 h.
[0019] In some embodiments, the sealing is performed using hot water sealing.
[0020] In some embodiments, the hot water sealing method comprises the following specific steps: immersing the aluminum alloy workpiece in water at 90° C. to 95° C. for 30 to 40 minutes, and then taking the workpiece out and washing and drying it with anhydrous ethanol.
[0021] More specifically, they include:
[0022] 1. Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0023] 2. Alkaline cleaning: Use 1-10 mL / L NaOH aqueous solution to clean with the assistance of ultrasonic waves for 10-15 minutes, then wash with water and alcohol.
[0024] 3. Pickling: Use a mixture of 1-10 mL / L HNO3 and 1-10 mL / L HF aqueous solution in a water bath at 40-60°C for 2-5 minutes, then wash with water and alcohol.
[0025] 4. Anodic oxidation: Use the hanging method to connect the graphite and the sample, with the graphite as the cathode and the sample as the anode, and immerse the two together in the electrolyte for the experiment. The electrolyte is 10-80g / L oxalic acid, 20-70g / L boric acid and 10-60g / L citric acid, the temperature is 25℃-60℃, the voltage is 20-50V, and the time is 1h-3h.
[0026] 5. Hot water sealing method. The specific steps are: immerse the aluminum sheet in 90℃ deionized water for 30 minutes, then take it out and clean it with anhydrous ethanol and blow it dry.
[0027] The second aspect of the present invention provides an aluminum alloy workpiece loaded with an oxide film prepared by the above method.
[0028] The third aspect of the present invention provides the application of the above-mentioned aluminum alloy workpiece loaded with oxide film in the field of aerospace or automobile manufacturing. More specifically, it includes the use of the aluminum alloy workpiece loaded with oxide film for manufacturing power transmission, radiator or heat exchanger.
[0029] Beneficial effects of the present invention
[0030] (1) The present invention uses 6063 aluminum alloy as the research object, and adopts anodizing technology to prepare a corrosion-resistant and anti-fouling oxide film on its surface. The purpose of the present invention is to provide a surface modification technology with simple process, less waste liquid discharge, less environmental pollution and low cost.
[0031] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0033] Figure 1 The macroscopic morphology and cross-sectional view of the oxide film layer, where (a) is the macroscopic morphology, and (b) is the cross-sectional view;
[0034] Figure 2 is the XRD pattern of the oxide film;
[0035] Figure 3 The SEM morphology of the oxide film;
[0036] Figure 4 Macroscopic morphology of 6063 aluminum alloy and oxide film layer in salt spray test, including (a) 6063 aluminum alloy, (b) oxide film layer.
[0037] Figure 5 Macroscopic morphology of scaling test of 6063 aluminum alloy and oxide film layer, including (a) 6063 aluminum alloy, (b) oxide film layer. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0039] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0040] In the following examples and comparative examples, the thyristor electroplating power supply (120V30mA) used for anodization was used, and the microstructure analysis of the oxide film was performed using a SU8600N electron microscope. The phase analysis of the oxide film was performed using a DX-2700BH multifunctional X-ray diffractometer (XRD). The diffraction conditions were Cu target, scanning voltage of 40kV, current of 40mA, scanning speed of 4° / min, step length of 0.02°, and scanning interval of 5-85°. The thickness of the anodized film was measured using a 4XC-1 metallographic microscope, and a 480 neutral salt spray test was performed on the anodized sample using a YWX1Q-90 salt spray test box produced by Wenzhou Jingcheng Measuring Equipment Co., Ltd. This test used CaCl2 and NaHCO3 to prepare a scaling liquid in a ratio of 1:2, and a scaling test was performed at a certain temperature (80°C) and flow rate (stirring speed of 400r / min) to simulate the real hard water state, and the unit area change was calculated by comparison using the gravimetric method.
[0041] Example 1
[0042] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0043] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0044] (2) Alkaline cleaning: Use 5 mL / L NaOH aqueous solution for cleaning under ultrasonic assistance for 10 minutes, and then wash with water and alcohol respectively.
[0045] (3) Acid washing: Use a mixture of 5 mL / L HNO3 and 5 mL / L HF aqueous solution in a 40°C water bath for 2 minutes, followed by water washing and alcohol washing.
[0046] (4) Anodic oxidation: Graphite and the sample are connected, with graphite as the cathode and the sample as the anode. The electrolyte is 70 g / L oxalic acid, 50 g / L boric acid and 40 g / L citric acid. The temperature is 40 °C, the voltage is 35 V, and the time is 2 h. The macroscopic morphology of the oxide film is as follows: Figure 1 As shown in (a), it is light yellow, bright and smooth, with a dense structure without defects and a ceramic texture. The thickness of the oxide film is about 23.91μm. Figure 1 As shown in (b).
[0047] (5) Figure 2 The diffraction patterns of the anodic oxide films prepared at different oxalic acid concentrations are shown in Figure 2. Figure 2 It can be seen that the characteristic peaks of Al (111), (200), (220), (311), and (222) appear at 2θ of 38.792°, 45.921°, 65.397°, 78.462°, and 82.627°, respectively. In addition, a mantou peak appears at around 10°, which is a typical XRD diffraction morphology of amorphous materials, namely Al2O3.
[0048] (6) Use SEM to characterize the oxide film layer, such as Figure 3 The figure shows the microscopic morphology of the oxide film layer, which proves that the oxide film layer is a nanoporous structure with randomly arranged and evenly distributed pores and a pore size in the range of 25 to 45 nm.
[0049] (7) The contact angle of the oxide film before sealing is 19.85°, and the contact angle after sealing is 134.12°, which has a certain degree of hydrophobicity.
[0050] (8) Figure 4The figure shows the macroscopic appearance of 6063 aluminum alloy and oxide film after 480h salt spray test. The 6063 surface is seriously corroded, while the oxide film has no obvious corrosion phenomenon. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0035g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about ten times that of the oxide film.
[0051] (9) Figure 5 The figure shows the macroscopic morphology of 6063 aluminum alloy and oxide film after scaling test. Scaling is obvious on the surface of 6063 aluminum alloy, while there is almost no scaling on the oxide film. The scale inhibition rate of 6063 is 83.12%, while the scale inhibition rate of the oxide film is 99.82%.
[0052] Example 2
[0053] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0054] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0055] (2) Alkaline cleaning: Use 10 mL / L NaOH aqueous solution for cleaning under ultrasonic assistance for 10 minutes, and then wash with water and alcohol respectively.
[0056] (3) Acid washing: using a mixture of 5% mL / L HNO3 and 5 mL / L HF aqueous solution in a 60°C water bath for 2 minutes, followed by water washing and alcohol washing.
[0057] (4) Anodic oxidation: Graphite and the sample were connected, with graphite as the cathode and the sample as the anode. The electrolyte was 60 g / L oxalic acid, 50 g / L boric acid and 40 g / L citric acid, 40 ° C, voltage 35 V, time 2 h. The oxide film has a dense structure and ceramic texture, and the thickness of the oxide film layer is about 18.62 μm.
[0058] (5) By Figure 2 It can be seen that the characteristic peaks of Al (111), (200), (220), (311), and (222) appear at 2θ of 38.792°, 45.921°, 65.397°, 78.462°, and 82.627°, respectively. In addition, a mantou peak appears at around 10°, which is a typical XRD diffraction morphology of amorphous materials, namely Al2O3.
[0059] (6) The oxide film layer has a nanoporous structure with randomly arranged and evenly distributed pores, and the pore diameter is in the range of 25 to 40 nm.
[0060] (7) The contact angle of the oxide film before sealing is 21.85°, and the contact angle after sealing is 138.25°, which has a certain degree of hydrophobicity.
[0061] (8) After 480 hours of salt spray test, there is no obvious corrosion phenomenon in the oxide film. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0038g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about 9 times that of the oxide film.
[0062] (9) After 5 hours of scaling test, the oxide film almost did not produce scaling. The scale inhibition rate of 6063 was 83.12%, while the scale inhibition rate of the oxide film was 99.65%.
[0063] Example 3
[0064] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0065] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0066] (2) Alkaline cleaning: Use 5 mL / L NaOH aqueous solution for cleaning under ultrasonic assistance for 10 minutes, and then wash with water and alcohol respectively.
[0067] (3) Acid washing: using a mixture of 5 mL / L HNO3 and 5 mL / L HF aqueous solution in a 60°C water bath for 2 min, followed by water washing and alcohol washing.
[0068] (4) Anodic oxidation: Graphite and the sample are connected, with graphite as the cathode and the sample as the anode. The electrolyte is 80g / L oxalic acid, 50g / L boric acid and 40g / L citric acid, 40°C, voltage 35V, time 2h. The oxide film has a dense structure and ceramic texture. The thickness of the oxide film layer is about 21.17μm.
[0069] (5) By Figure 2 It can be seen that the characteristic peaks of Al (111), (200), (220), (311), and (222) appear at 2θ of 38.792°, 45.921°, 65.397°, 78.462°, and 82.627°, respectively. In addition, a mantou peak appears at around 10°, which is a typical XRD diffraction morphology of amorphous materials, namely Al2O3.
[0070] (6) The oxide film layer has a nanoporous structure with randomly arranged and evenly distributed pores, and the pore diameter is in the range of 20 to 40 nm.
[0071] (7) The contact angle of the oxide film before sealing is 20.36°, and the contact angle after sealing is 134.36°, which has a certain degree of hydrophobicity.
[0072] (8) After 480 hours of salt spray test, there is no obvious corrosion phenomenon in the oxide film. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0040g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about 8 times that of the oxide film.
[0073] (9) After 5 hours of scaling test, the oxide film showed almost no scaling. The scale inhibition rate of 6063 was 83.12%, while the scale inhibition rate of the oxide film was 99.71%.
[0074] Example 4
[0075] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0076] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0077] (2) Alkaline cleaning: Use 5 mL / L NaOH aqueous solution for cleaning under ultrasonic assistance for 10 minutes, and then wash with water and alcohol respectively.
[0078] (3) Acid washing: using a mixture of 5 mL / L HNO3 and 5 mL / L HF aqueous solution in a 60°C water bath for 2 min, followed by water washing and alcohol washing.
[0079] (4) Anodic oxidation: Graphite and the sample were connected, with graphite as the cathode and the sample as the anode. The electrolyte was 70 g / L oxalic acid, 50 g / L boric acid and 40 g / L citric acid, 40 ° C, voltage 40 V, time 2 h. The oxide film has a dense structure and ceramic texture. The oxide film is mainly composed of Al2O3, and the thickness of the oxide film layer is about 28.85 μm.
[0080] (5) The oxide film layer has a nanoporous structure with randomly arranged and evenly distributed pores, and the pore diameter is in the range of 22 to 35 nm.
[0081] (6) The contact angle of the oxide film before sealing is 15.85°, and the contact angle after sealing is 128.20°, which has a certain degree of hydrophobicity.
[0082] (7) After 480 hours of salt spray test, there is no obvious corrosion phenomenon in the oxide film. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0039g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about 9 times that of the oxide film.
[0083] Example 5
[0084] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0085] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0086] (2) Alkaline cleaning: Use 5 mL / L NaOH aqueous solution for cleaning under ultrasonic assistance for 10 minutes, and then wash with water and alcohol respectively.
[0087] (3) Acid washing: using a mixture of 5 mL / L HNO3 and 5 mL / L HF aqueous solution in a 60°C water bath for 2 min, followed by water washing and alcohol washing.
[0088] (4) Anodic oxidation: Graphite and the sample were connected, with graphite as the cathode and the sample as the anode. The electrolyte was 70 g / L oxalic acid, 50 g / L boric acid and 40 g / L citric acid, 40 ° C, voltage 30 V, time 2 h. The oxide film has a dense structure and ceramic texture. The oxide film is mainly composed of Al2O3, and the thickness of the oxide film layer is about 26.78 μm.
[0089] (5) The oxide film layer has a nanoporous structure with randomly arranged and evenly distributed pores, and the pore diameter is in the range of 25 to 38 nm.
[0090] (6) The contact angle of the oxide film before sealing is 15.85°, and the contact angle after sealing is 128.20°, which has a certain degree of hydrophobicity.
[0091] (7) After 480 hours of salt spray test, there is no obvious corrosion phenomenon in the oxide film. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0036g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about 9 times that of the oxide film.
[0092] (8) After 5 hours of scaling test, the oxide film showed almost no scaling. The scale inhibition rate of 6063 was 83.12%, while the scale inhibition rate of the oxide film was 99.07%.
[0093] Example 6
[0094] The purpose of the present invention is to provide an aluminum alloy surface modification anodizing technology with simple process, less waste liquid discharge, less environmental pollution and low cost. The specific steps are as follows:
[0095] (1) Mechanically clean the aluminum alloy, wash with water, and then clean with alcohol.
[0096] (2) Alkaline cleaning: Use 5% volume fraction NaOH aqueous solution to clean with the assistance of ultrasonic waves for 10 minutes, and then wash with water and alcohol respectively.
[0097] (3) Pickling: using a mixture of 5% by volume HNO3 and 5% by volume HF aqueous solution in a 60°C water bath for 2 minutes, followed by water washing and alcohol washing.
[0098] (4) Anodic oxidation: Graphite and the sample were connected, with graphite as the cathode and the sample as the anode. The electrolyte was 70 g / L oxalic acid, 50 g / L boric acid and 40 g / L citric acid, 40 ° C, voltage 40 V, time 1.5 h. The oxide film has a dense structure and ceramic texture. The oxide film is mainly composed of Al2O3, and the thickness of the oxide film layer is about 16.31 μm.
[0099] (5) The oxide film layer is a nanoporous structure with randomly arranged and evenly distributed pores, and the pore diameter is in the range of 25 to 40 nm.
[0100] (6) The contact angle of the oxide film before sealing is 15.85°, and the contact angle after sealing is 118.20°, which has a certain degree of hydrophobicity.
[0101] (7) After 480 hours of salt spray test, there is no obvious corrosion phenomenon in the oxide film. As time goes by, the color of the oxide film becomes lighter. The corrosion rate of the oxide film is +0.0042g / (m 2 ·d day), while the corrosion rate of the substrate is +0.0321g / (m 2 ·d), the corrosion rate of the substrate is about 8 times that of the oxide film.
[0102] (8) After 576 hours of immersion test, the corrosion rate of the oxide film is +0.458mg / (dm 2 ·day), while the corrosion rate of the aluminum substrate is +2.900mg / (dm 2 ·day), the corrosion rate of the substrate is about 6 times that of the oxide film.
[0103] Comparative Example 1
[0104] The difference from Example 1 is that no boric acid is added, and the electrolyte is 70 g / L oxalic acid and 40 g / L citric acid. The corrosion rate of the oxide film is +0.0054 g / (m 2 ·d day), the scale inhibition rate of the oxide film was 95.32%.
[0105] Comparative Example 2
[0106] The difference from Example 1 is that oxalic acid is not added, and the electrolyte is 50 g / L boric acid and 40 g / L citric acid. The corrosion rate of the oxide film is +0.0049 g / (m 2 ·d day), the scale inhibition rate of the oxide film was 96.42%.
[0107] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that compared with the oxalic acid-citric acid system and the boric acid-citric acid system, the oxalic acid-boric acid-citric acid system can better improve the corrosion resistance and scale inhibition of the oxide film.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing an oxide film having corrosion resistance and scale inhibition properties, characterized in that: include: Cleaning the aluminum alloy workpiece; Mix 10-80 g / L oxalic acid, 20-70 g / L boric acid and 10-60 g / L citric acid to prepare an electrolyte; Anodizing the cleaned aluminum alloy workpiece in the electrolyte to obtain an oxide film; The oxide film is sealed to obtain the product.
2. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The cleaning includes: water cleaning, alcohol cleaning, alkali cleaning and acid cleaning.
3. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The specific steps of the alkaline washing include: using 1-10 mL / L NaOH aqueous solution, washing under the assistance of ultrasound for 10-15 minutes, and then washing with water and alcohol.
4. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The specific steps of the pickling include: using a mixture of 1-10 mL / L HNO3 and 1-10 mL / L HF aqueous solution in a water bath at 40-60°C for 2-5 minutes, followed by water washing and alcohol washing.
5. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The anodic oxidation adopts a hanging method to connect graphite and a sample, wherein the graphite serves as a cathode and the aluminum alloy workpiece serves as an anode.
6. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The temperature of the anodizing is 25° C. to 60° C., the voltage is 20 to 50 V, and the time is 1 hour to 3 hours.
7. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The sealing method is hot water sealing.
8. The process for preparing an oxide film having corrosion resistance and scale inhibition properties according to claim 1, characterized in that: The specific steps of the hot water sealing method are: immersing the aluminum alloy workpiece in water at 90° C.-95° C. for 30-40 minutes, and then taking it out and washing it with anhydrous ethanol and drying it.
9. An aluminum alloy workpiece loaded with an oxide film prepared by the method according to any one of claims 1 to 8.
10. Application of the aluminum alloy workpiece loaded with oxide film according to claim 9 in the fields of aerospace and automobile manufacturing, characterized in that: The aluminum alloy workpiece loaded with an oxide film is used for manufacturing power transmission, a radiator or a heat exchanger.